Improving E-Commerce Application through Sense of Agency of a Calibrated Interactive VR Application - Abdul Rahim, Nurul Aiman; Norasikin, Mohd Adili; Maksom, Zulisman (Universiti Utara Malaysia Press, 2022)
Virtual reality (VR) technologies create and control different virtual worlds instead of the actual environment, and this contributes to the feeling of control known as the sense of agency (SoA). The SoA exists from the contrast between the expected sensory consequence of one’s action from the efference copy and the real sensory effects. However, the size representation of objects differs between the physical and virtual worlds due to certain technical limitations, such as the VR application’s virtual hand not reflecting the user’s actual hand size. These limitations will incur low quality of perception and SoA for digital application. This paper proposed a proof-of-concept of an interactive e-commerce application that incorporates VR capability and size calibration mechanism. The mechanism used a calibration method based on the reciprocal scale factor from the virtual object to its real counterpart. A study of SoA focusing on user perception and interaction was conducted. The proposed method was tested on 22 participants who were also online shopping users. Nearly half of the participants (45%) bought online products frequently, with at least one transaction per day. The outcome indicated that the proposed method improved 47 percent of user perception and interaction as compared to the conventional e-commerce application with its static texts and images. The proposed method is rudimentary yet effective and can be easily implemented in any digital field.